Examining emotion dysregulation within police–community interactions - Makin, David A. (International journal of police science & management, 2025)
This is a precursor study of de-escalation and non-escalation. Using an interdisciplinary framework, we code emotion dysregulation derived from body-worn camera footage. We then test the influence of individual, situational, and environmental predictors on emotion dysregulation. We apply systematic social observation and systematic social event modeling to body-worn camera footage associated with 568 separate interactions for a small agency in the United States; involving more than 11,000 minutes of contact between police officers and community members. The largest predictor of emotion dysregulation on the part of the officer is dysregulation on the part of the person of interest. Given the role of emotions in decision-making and their largely neglected state in the policing literature, these results demonstrate the utility of drawing upon the rich data contained within body-worn camera footage. Results also highlight contextual factors influencing dysregulation.